ACADEMIC STRESS AND ITS ASSOCIATION WITH DEPRESSION AMONG HIGH SCHOOL STUDENTS IN VINH LONG PROVINCE (Vietnam Journal of Community Medicine, 2026)
Objectives: To determine the prevalence and levels of academic stress using the ESSA scale among high school students; to analyze the association between academic stress and depression; to identify factors associated with academic stress (individual, family, and school characteristics).Materials and methods: An analytical cross-sectional study was conducted on 919 students in grades 10-12 at four high schools in Vinh Long province, with data collected from October to December 2023. The ESSA was used to assess academic stress, and the CES-D was used to assess depression.Results: The prevalence of low, medium, and high academic stress was 42.8%, 35.6%, and 21.7%, respectively. The prevalence of depression (CES-D > 25) was 12.2%. There was a strong positive association between these two issues: students with high academic stress had 5.81 times higher odds of depression compared to the low-stress group (OR = 5.81; p < 0.001). Multivariate regression analysis identified three independent risk factors increasing academic stress: female gender (OR = 2.20), family verbal abuse/humiliation (OR = 1.95), and being scolded/threatened by teachers (OR = 2.19). No statistically significant association was found between academic performance (grading) and the level of academic stress.Conclusion: More than one-fifth of students are enduring high levels of academic stress, which is a critical factor contributing to depression. This burden does not depend on the students’ academic ability but is primarily driven by negative interactions (psychological violence) from the family and school. Future interventions should focus on improving pedagogical communication skills and family interaction dynamics to minimize risks.
Keywords: Academic stress, ESSA, depression, verbal abuse, high school students, Vinh Long.